(untitled) (Tribhuvan University Journal of Microbiology, 2023)
Objectives: To screen and evaluate antimicrobial activity of crude ethanol extracts of medicinal plants against various bacteria. Methods: The study was conducted from February - August 2018 in Pinnacle college, Lalitpur with plan to collect Seven different herbs species; Acorus calamus (Bojho), Aloe vera (Ghiu Kumari), Artermisia indica (Titepate), Azadirachta indica (Neem), Mentha arvensis (Pudhina), Zanthoxylum armatum (Timur) and Zingiber officinale (Ginger) were subjected to 70% ethanol soxhlet extraction, then extract then heated at 78.37°C to remove ethanol, working solution was prepared in DMSO. Test organisms included mainly enteric isolates i.e. Escherichia coli, Pseudomonas aeruginosa, Klebsiella oxytoca, Salmonella Typhi and Staphylococcus aureus were selected. The Antibiotic Susceptibility tests of isolates were done by of Modified Kirby Bauer disc diffusion method. The antimicrobial activities of the extracts were determined by Agar well diffusion technique. Minimum Bactericidal Concentration (MBC) was determined by dilution technique. Results: Among 7 plants that were tested, 6 plants were found to have activity against test bacteria. Acorus calamus 3/5(60%) was effective against test bacteria. Azadirachta indica and Menthe arvensis inhibited 2/5 (40%). Aloevera and Artermisia indica were effective against S aureus only 1/5(20%) and Zingiber officinale had no antibacterial effects over any tested bacteria. S. aureus was the most susceptible Gram positive bacteria meanwhile K. oxytoca stood among Gram negative, emerged as the most resistant species. S. aureus showed ZOI with 6 plant extracts excluding ginger P. aeruginosa was inhibited by Acorus calamus, Azadirachta indica and Mentha arvensis. The largest ZOI of 15 mm was obtained with Zanthoxylum armatum acting upon S. aureus. While, the smallest diameter of 8 mm was showed by Acorus calamus against S. Typhi. The lowest MBC was given 15.63 mg/ml by Mentha arvensis and Azadirachta indica against Pseudomonas aeruginosa while, Artermisia indica against S. aureus. Conclusion: Medicinal plants should be possible medication in the future to combat pathogens.